A Collection Profile Analysis and Possible Methodology Based on Current and Projected Needs. (3rd April 2021) - Crayne, Janet
ABSTRACT: Thanks to the ease of access and functionality facilitated by the internet, WorldCat and its contents have acquired more expansive meaning and are now being viewed in more global terms. More specifically, WorldCat is increasingly used to create portraits of different institutions' holdings for comparative purposes. Such comparisons might be used to inform very real, large-scale collection decisions and strategies, particularly in the context of today's earnest discussions about collective collecting. This article questions the wisdom of relying on WorldCat in this way and proposes an alternative approach.